2016
DOI: 10.1007/s11695-016-2124-1
|View full text |Cite
|
Sign up to set email alerts
|

The Controversy of the Most Proper Time for Pregnancy After Bariatric Surgery: a Review of Ten Cases

Abstract: The results of the present study suggest revising setting a contraindication for conception for patients undergoing bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Norgaard et al found no difference in the prevalence of SGA prior to, or after, 18 months (level 2++). Other studies also did not find a difference in gestational outcomes according to surgery to conception interval …”
Section: Evidence and Recommendationsmentioning
confidence: 86%
“…Norgaard et al found no difference in the prevalence of SGA prior to, or after, 18 months (level 2++). Other studies also did not find a difference in gestational outcomes according to surgery to conception interval …”
Section: Evidence and Recommendationsmentioning
confidence: 86%
“…Women with class III obesity account for 73–80% of these patients and 43% are of reproductive age [ 2 ]. Bariatric surgery reduces associated diseases, modifies the regularity of menstrual cycles, increases fertility and thereby favors the occurrence of pregnancy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that contributes to VAD is an increase in tissue adiposity [ 13 ]. In this context, the permanence of overweight and/or obesity in pre-pregnancy, a frequent occurrence after bariatric surgery, and gestational weight gain above the recommended range, are considered determining factors for gestational adverse outcomes [ 1 , 4 , 14 , 15 ] and can still contribute to the worsening of the nutritional status of vitamin A.…”
Section: Introductionmentioning
confidence: 99%
“…However, cultural and geographical issues, such as light exposure, work-shifts, diet, and sleep pattern affect menstrual cycles, as well as obesity status [9][10][11]; thus, it is essential to separately study the prevalence of menstruation disturbances and their association with obesity in different nations. Iranian studies addressing the prevalence and the factors associated with menstrual disorders in Iranian women are scarce.…”
Section: Introductionmentioning
confidence: 99%